Chairman - Masouras, Panicos (My University, 2026)
Chairing the organizing committee of Robotex Cyprus the largest robotics event in Cyprus established in 2017. The 2019 edition of the event gathered more than 1000 robotics players, 95 coaches and was supported by more than 90 volunteers from universities, professional association and private organizations.